The Effectiveness of the Generative Model in Learning Synonyms and Antonyms in English Language at Kingdom of Saudi Arabia - Mohamed Ahmed Mohamed Osman, Hatim; Mohamed Abd Allah Al Shahrani, Salwa (Journal of College of Education, 2022)
The research aims to identify the effectiveness of using the generative model in learning synonyms and antonyms in English language course for secondary second-grade female students in Bisha governorate. It used quasi-experimental approach. The research reached many results: That the value of ETA square in the levels of remembering, understanding and application, as well as the total score of the test reached (0.38, 0.66, 0.68, 0.77) respectively, and it is all higher than (0.14), which indicates a significant impact of using the proposed unit in learning synonyms and antonyms in light of the Generative Learning Model. The research recommended using Generative Learning Model in the educational process because of its proven effectiveness in developing the level of learning synonyms and antonyms.
Keywords: Keywords: Generative Model - Synonyms – Antonyms